Multiple Intelligence Levels in Engineering Students: A Comparative Analysis between Majors and Faculties at the Technological University of Panama - Barría, Nicole (2023)
Background. One of the challenges of contemporary education is to develop competent students who can function effectively in the increasingly competitive world. This research focuses on the study of intelligence from the perspective of Howard Gardner’s multidisciplinary perspective. Objective. This study aimed to determine and compare the level of development of multiple intelligences in engineering students at the Universidad Tecnológica de Panamá [Technological University of Panama -UTP] by faculty and major in order to provide recommendations to improve teaching methods. Method. This descriptive-comparative field research with a quantitative approach consisted of 85 students in their final year of engineering studies. They were administered a questionnaire adapted from the IAMI-R psychological instrument. After data collection, descriptive and comparative statistical analyzes were performed using Minitab. Results. The results indicate that linguistic and logical-mathematical intelligences are the most prevalent in the students of the different faculties at the UTP. Conversely, bodily-kinesthetic and naturalistic intelligences are among the two least developed for 83% of the faculties, except for the Faculty of Science and Technology, where naturalistic intelligence is the third least developed. Conclusion. It is concluded that there are significant differences in the level of development of multiple intelligences between faculties and majors to which the UTP students belong. The study determines that bodily-kinesthetic and naturalistic intelligences are among the least developed. For this reason, it is recommended that the university implements activities to develop these intelligences, such as dramatization or studying body language.